The Relationship Of Workload And Completeness Spiritual Care Documentation In Nurses In Islamic Hospital Mataram - Zulkahfi, Zulkahfi; Hadi, Irwan; Halid, Sopian; Idri, Baiq Nurainun Apriani; Maliki, Imam (International Journal of Health Sciences, 2024)
Documentation is an essential element in accountability for the performance of the nursing profession after performing nursing interventions directly to the client. Findings at the hospital showed that nursing documentation forms have been prepared not complete or not complete unfilled. Nurses more does the work of coordination and an abundance of authority. So that we need to know about correlation of nurses workload with nursing documentation. The method used is descriptive correlation with cross sectional approach. The number of samples in this study were as many as 56 people with purposive sampling method. Analysis of data using statistical test of Rank Spearman. The results of this study showed the majority of the workload of nurses in middle category (37.5%) and most of the documentation of nursing care nurses perform incomplete documentation (67.9), while the Spearman Rank test results show the significance value of 0.011 (P <0,05), which shows there is a relationship between the workload of nurses and nursing documentation. Nurses are required to conduct complete care documentation for record of the whole action is given to the patient can be used as evidence of nursing care has been done correctly, precise, and comprehensive.